Severe congenital cutis laxa: Identification of novel homozygous LOX gene variants in two families. Issue 2 (25th April 2021) - McKenzie, Fiona; Mina, Kym; Callewaert, Bert; Beyens, Aude; Dickinson, Jan E.; Jevon, Gareth; Papadimitriou, John; Diness, Birgitte Rode; Steensberg, Jesper Norman; Ek, Jakob; Baynam, Gareth
Abstract: We report three babies from two families with a severe lethal form of congenital cutis laxa. All three had redundant and doughy‐textured skin and two siblings from one family had facial dysmorphism. Echocardiograms showed thickened and poorly contractile hearts, arterial dilatation and tortuosity. Post‐mortem examination in two of the babies further revealed widespread ectasia and tortuosity of medium and large sized arteries, myocardial hypertrophy, rib and skull fractures. The presence of fractures initially suggested a diagnosis of osteogenesis imperfecta. Under light microscopy bony matrices were abnormal and arterial wall architecture was grossly abnormal showing fragmented elastic fibres. Molecular analysis of known cutis laxa genes did not yield any pathogenic defects. Whole exome sequencing of DNA following informed consent identified two separate homozygous variants in the LOX (Lysyl Oxidase) gene. LOX belongs to the 5‐lysyl oxidase gene family involved in initiation of cross‐linking of elastin and collagen. A mouse model of a different variant in this gene recapitulates the phenotype seen in the three babies. Our findings suggest that the LOX gene is a novel cause of severe congenital cutis laxa with arterial tortuosity, bone fragility and respiratory failure. Abstract : ​